Endoscopic ultrasound‐guided fine needle aspiration (EUS‐FNA) contributes to a triple‐negative test in preoperative screening of pancreatic cysts. Issue 6 (10th December 2013) - Wu, Roseann I.; Yoon, Won Jae; Brugge, William R.; Mino‐Kenudson, Mari; Pitman, Martha B.
Abstract : BACKGROUND: Endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) of pancreatic cysts obtains cyst fluid for cytologic and biochemical analysis, which may determine whether the cyst is mucinous and malignant, contributing to patient management. Despite this added value, EUS‐FNA remains controversial in the preoperative assessment of pancreatic cysts. The objective of this study was to assess the utility of EUS‐FNA in a cohort of small pancreatic cysts that were benign on imaging studies. METHODS: All pancreatic cysts that underwent initial EUS‐FNA in 2006 and 2007 were retrospectively analyzed. Ninety‐two patients with pancreatic cysts met the inclusion criteria. Patients who had high‐risk or worrisome features on imaging studies were excluded. Cytology, histology, and cyst fluid analysis data were collected. The main outcome measurements were radiologic and clinical follow‐up as well as cytopathologic and histologic results. RESULTS: EUS‐FNA supported a diagnosis of a mucinous cyst in 38 of 92 patients (41%) by carcinoembryonic antigen (CEA) measurement and/or cytology. Cytology demonstrated an absence of high‐grade atypia (HGA) in 89 of 92 patients (97%). The mean follow‐up was 4.4 years (range, 0‐7.7 years), during which 6 cysts were surgically resected and 16 cysts were resampled by at least 1 subsequent EUS‐FNA. The overall negative predictive value of cytologic examination for HGA was 99%. CONCLUSIONS: EUS‐FNA is a screening test that contributes to a triple‐negative test for pancreatic cysts—no high‐risk stigmata, no worrisome features, and no HGA on cytology—providing a negative predictive value of 99% for conservative management. Cancer (Cancer Cytopathol) 2014;122:412–419 . © 2013 American Cancer Society . Abstract : Endoscopic ultrasound‐guided fine‐needle aspiration is a screening test that contributes to a triple‐negative result for pancreatic cysts—no high‐risk stigmata, no worrisome features, and no high‐grade atypia on cytology—providing a high negative predictive value for conservative management.